2022
DOI: 10.1088/1674-1056/ac4cc6
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening and softening in gradient nanotwinned FCC metallic multilayers

Abstract: The plastic-deformation behaviors of gradient nanotwinned (GNT) metallic multilayers are investigated at the nanoscale via molecular dynamics simulation. The evolution law of deformation behaviors of GNT metallic multilayers with different stacking fault energies (SFEs) during nanoindentation is revealed. The deformation behavior transforms from the dislocation dynamics to the twinning/detwinning in the GNT Ag, Cu, to Al with SFE increasing. In addition, it is found that the GNT Ag and GNT Cu strengthen in cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Molecular dynamics (MD) simulation provides an alternative method to experiments, which plays an important role in understanding the deformation mechanism in metallic materials. [35][36][37][38] Actually, the mechanical properties of the crystalline/amorphous nanolaminates have been investigated in the past few years using MD simulation. [39][40][41][42] Tran and Fang [39] reported that the plastic deformation zones increase as the thickness of each layer decreases in crystalline/amorphous Cu/CuTa nanolaminates.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation provides an alternative method to experiments, which plays an important role in understanding the deformation mechanism in metallic materials. [35][36][37][38] Actually, the mechanical properties of the crystalline/amorphous nanolaminates have been investigated in the past few years using MD simulation. [39][40][41][42] Tran and Fang [39] reported that the plastic deformation zones increase as the thickness of each layer decreases in crystalline/amorphous Cu/CuTa nanolaminates.…”
Section: Introductionmentioning
confidence: 99%